Scabies Norvegica in infant - Mergita Ferizi; Antigona Gercari; Mybera Ferizi (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2023)
Introduction: Crusted scabies are a rare manifestation of scabies characterized by uncontrolled proliferation of mites in the skin. Crusted scabies are a severe variant of highly contagious scabies. Various cutaneous, neurologic and immunologic diseases have been described to predispose to crusted scabies. Case presentation: The presented case is a 7-month-old male. He was hospitalized at the Clinic of Dermatovenerology, due to hyperkeratotic changes in the palms and food, papules throughout the body, and nail changes all of these accompanied by scratching. Initially, it was diagnosed as atopic dermatitis, hyperkeratosis palmoplantaris, and onychomycosis mani. The changes had started to appear five months ago. Also, the mother of the child presents the papules throughout the body, also associated with itching as classical scabies. Conclusion: Crusted scabies are a severe variant of highly contagious scabies. Is known the failure of the immune system to suppress the proliferation of the mite is an important cause of crusted scabies development. Crusted scabies usually do not present as an acute eruption as in classical scabies. The eruption is slow in onset and insidious in progression. In the present case, we learned that in the stimulation of the condition, there was a major role in the application of topically fluoride steroids.